Diagnostic value of bronchoscopy in Sars-Cov-2 infection: a systematic review - Raza, Hussain Ahmed; Raja, Mohummad Hassan Raza; Bain, Paul Arthur; Bedi, Harmeet; Salam, Rehana; Jamil, Bushra; Shafiq, Majid (Journal of the Pakistan Medical Association, 2022)
Objective: To investigate the diagnostic performance of bronchoscopy in patients with coronavirus disease 2019 infection. Method: The systematic review was conducted in April 2021 and comprised search of published articles and preprint servers for original articles assessing diagnostic performance of bronchoscopy in patients with suspected coronavirus disease 2019 infection. The primary outcome of interest was diagnostic sensitivity of bronchoalveolar lavage in the patients The quality of each study was assessed using the Quality Assessment, Data Abstraction and Synthesis-2 tool. Results: Of the 29 full-text articles assessed for eligibility, 4(13.8%) were included collectively comprising 209 patients who had undergone bronchoalveolar lavage. Mean sensitivity of bronchoalveolar lavage was 83.5% +/- 10.63 (range: 68.2-940%). Overall, the 4 studies had an unclear or low risk of bias. Conclusion: Limited data suggested that bronchoscopy with bronchoalveolar lavage did not have reliably higher diagnostic sensitivity than that reported for either nasopharyngeal or oropharyngeal swabs. Key Words: Bronchoscopy and interventional techniques, COVID-19, Diagnostic techniques.